An oxygen-doped hard carbon electrode material for sodium ion batteries and its preparation method and application
Through the preparation method of oxygen-doped hard carbon electrode material, the problem of low sodium storage capacity of graphite-type carbon materials in sodium ion batteries is solved, and an oxygen-doped hard carbon electrode material with high sodium storage capacity and good electrochemical performance is achieved Preparation.
Patent Information
- Application Number
- CN202410915514.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-09
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-07-09
AI Technical Summary
The existing graphite carbon materials have a large energy barrier in sodium ion batteries, which leads to the low-level carbon materials being embedded in carbon materials with low layer spacing. The problem.
Through the preparation method of oxygen-doped hard carbon electrode material, the epoxy bond of epoxy organic molecules and the hydroxyl group of carbon source organic molecules are used to form ether bonds, and oxygen functional cross-linking hard carbon is prepared by etherification cross-linking, and hydrogen argon is used to form etheric bonds. The heat treatment and high-temperature carbonization process optimize the cross-linked structure and increase the carbon layer spacing.
The sodium storage specific capacity of oxygen-doped hard carbon electrode materials is improved, the sodium diffusion path is shortened, the electrochemical reaction active site is increased, the electrochemical performance is significantly improved, and the preparation method of high-level spacing hard carbon is simplified.
Smart Images

Figure CN118771353B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of battery electrode materials, and in particular relates to an oxygen-doped hard carbon electrode material for a sodium ion battery, and a preparation method and application thereof. Background Art
[0002] The information disclosed in this background section is intended to enhance understanding of the overall background of the invention and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] With the irreversible consumption of fossil fuels and serious pollution to the environment, the development and application of green new energy has become a hot topic of research. Among various energy storage devices, electrochemical energy storage devices represented by sodium ion batteries are widely used in daily life due to their advantages such as high specific capacity, low device cost, and no influence of environmental factors. Hard carbon is a very potential negative electrode material for sodium ion batteries. Although graphite carbon materials have many advantages, the energy barrier in the process of sodium ion deintercalation and intercalation of carbon atomic layers is large, and sodium ions are not suitable for embedding into carbon materials with low interlayer spacing, which leads to the problem of low specific capacity of carbon material negative electrode, which greatly restricts the application of graphite carbon materials in sodium ion batteries. In addition, as a low interlayer spacing carbon material, graphite carbon material has a significant problem of high first irreversible capacity. Therefore, it is a very meaningful work to improve the inherent defects of carbon by optimizing the preparation method of carbon material interlayer spacing and rationally designing the microstructure.
[0004] Studies have shown that cross-linking of hard carbon precursors can effectively increase the interlayer spacing of carbon materials obtained after pyrolysis. However, most of the current hard carbon preparation processes have shortcomings such as complex processes, low yields, and the use of templates that are difficult to remove. Summary of the invention
[0005] In view of the shortcomings of the prior art, the first object of the present invention is to provide a method for preparing an oxygen-doped hard carbon electrode material for a sodium ion battery. The preparation method has the advantages of simple operation, easy control, low price of reagents used, and green environmental protection, and is easy to prepare low-cost and high-performance hard carbon on a large scale.
[0006] The second object of the present invention is to provide the above-mentioned oxygen-doped hard carbon electrode material for sodium ion batteries. The oxygen-doped hard carbon electrode material for sodium ion batteries has a higher sodium storage capacity, a shorter sodium diffusion path, more electrochemical reaction active sites, and good electrochemical performance.
[0007] The third object of the present invention is to provide an application of the above-mentioned oxygen-doped hard carbon electrode material for sodium ion batteries.
[0008] To achieve the above object, the present invention adopts the following technical solution:
[0009] A method for preparing oxygen-doped hard carbon for sodium ion batteries, the preparation method comprising the following steps:
[0010] (1) dissolving a carbon source and a cross-linking agent in an epoxy organic solvent, adding a catalyst, and heating to obtain a mixed solution;
[0011] (2) adding an alkaline solution to the mixed solution obtained in step (1) to carry out a cross-linking reaction, and obtaining a cross-linked solid after drying;
[0012] (3) placing the cross-linked solid obtained in step (2) in a hydrogen-argon mixed atmosphere and heating it to obtain a pretreated cross-linked solid;
[0013] (4) Annealing the original cross-linked solid obtained in step (3) to obtain the oxygen-doped hard carbon electrode material for sodium ion battery.
[0014] Furthermore, in step (1), the carbon source is asphalt, lignin or cellulose.
[0015] Furthermore, in step (1), the cross-linking agent is m-phenylenediamine, p-phenolamine, melamine, urea-formaldehyde resin or phosphoric acid.
[0016] Furthermore, in step (1), the epoxy organic solvent is epichlorohydrin, propylene oxide, epifluorohydrin, epibromohydrin or 3,4-epoxy-1-butene.
[0017] Furthermore, in step (1), the catalyst is tetramethylammonium bromide, tetramethylammonium chloride, dodecyltrimethylammonium chloride or benzyltriethylammonium chloride.
[0018] Furthermore, in step (1), the mass volume ratio of the carbon source, the crosslinking agent, the catalyst and the epoxy organic solvent is 1 g: (0.05-2) g: (0.01-1) g: (1.12-56) mL. The liquid phase transfer catalyst used is used to increase the reaction rate between the epoxy organic molecules and the alkaline solution.
[0019] Furthermore, in step (1), the heating temperature is 40-117° C. and the heating time is 0.1-20 h.
[0020] Furthermore, in step (2), the alkaline solution is a sodium hydroxide solution or a potassium hydroxide solution.
[0021] Furthermore, in step (2), the mass concentration of the alkaline solution is 0.1-30%.
[0022] Furthermore, the volume ratio of the epoxy organic solvent in step (1) to the alkaline solution in step (2) is 1:(0.1-100).
[0023] Furthermore, in step (2), the temperature of the cross-linking reaction is 30-117° C., and the time is 0.1-10 h.
[0024] Furthermore, in step (3), the hydrogen-argon mixed atmosphere is composed of hydrogen and argon in a volume ratio of (1-0.01):1.
[0025] Furthermore, in step (3), the heating temperature is 200-600°C, the heating time is 0.1-5 h, and the heating rate is 1-10°C / min.
[0026] Furthermore, in step (4), the annealing treatment is carried out in an inert atmosphere; the annealing treatment temperature is 800-1600°C, the time is 0.5-6 h, and the heating rate is 1-10°C / min.
[0027] Furthermore, the inert atmosphere is nitrogen or argon.
[0028] The present invention utilizes the epoxy bond of epoxy organic molecules to react with the hydroxyl group in the carbon source organic molecules to form an ether bond, and prepares oxygen functional group cross-linked hard carbon through etherification cross-linking. The oxygen functional groups in the cross-linking connect the independent carbon source organic molecules. In addition, the epoxy bonds can be further cross-linked and modified with other cross-linking agents to optimize the structure. The cross-linked structure can also be further optimized by hydrogen-argon heat treatment. The high-temperature carbonization process undergoes a solid-state pyrolysis process, which avoids the rearrangement of the carbon layer during the carbonization process and increases the carbon layer spacing. This hard carbon with high oxygen content and large layer spacing structure not only increases its sodium storage specific capacity, shortens the sodium diffusion path, and increases the electrochemical reaction active sites, but also significantly simplifies the preparation method of high-layer spacing hard carbon, and is easy to large-scale prepare low-cost and high sodium storage performance hard carbon, which has important application significance in battery electrode material technology, especially in the field of sodium ion batteries.
[0029] The oxygen-doped hard carbon electrode material for sodium ion battery prepared by the above method is formed by carbon elements and oxygen elements in a suitable proportion; the surface of the oxygen-doped hard carbon electrode material is blocky; and the surface of the oxygen-doped hard carbon electrode material contains mesopores.
[0030] Furthermore, the pore size distribution of the mesopores is mainly between 1-30 nm, and the rich microporous structure can significantly increase the electroactive sites of the electrode material and improve the ion transfer rate.
[0031] The application of the above-mentioned oxygen-doped hard carbon electrode material for sodium ion batteries, the oxygen-doped hard carbon electrode material can be used in the field of sodium ion batteries.
[0032] Beneficial effects: The technical solution for preparing oxygen-doped hard carbon electrode materials for sodium ion batteries of the present invention has the advantages of simple operation, low price and easy acquisition of experimental raw materials, and is easy to prepare low-cost and high-performance hard carbon on a large scale; the oxygen-doped hard carbon electrode material for sodium ion batteries prepared by the technical solution of the present invention has the characteristics of high oxygen content and increased carbon layer spacing, which increases the sodium storage capacity of the oxygen-doped hard carbon electrode material, shortens the sodium diffusion path, and increases the active sites of electrochemical reactions. The oxygen-doped hard carbon electrode material has good electrochemical properties and has important application significance in the field of battery electrode material technology, especially sodium ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. The embodiments of the present invention are described in detail below in conjunction with the accompanying drawings, wherein:
[0034] Figure 1 is an X-ray diffraction pattern of the oxygen-doped hard carbon electrode material prepared in Example 1;
[0035] Figure 2 This is a scanning electron microscope image of the oxygen-doped hard carbon electrode material prepared in Example 1;
[0036] Figure 3 Statistical graph of the charge and discharge specific capacity of a sodium ion battery assembled with the oxygen-doped hard carbon electrode materials prepared in Examples 1-4 and the pitch block carbon material prepared in Comparative Example 1 at a current density of 30 mA / g. DETAILED DESCRIPTION
[0037] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] Example 1
[0039] (1) Grind the asphalt with a planetary ball mill, dissolve 1 g of asphalt powder and 0.2 g of melamine in 10 mL of epichlorohydrin, and after complete dissolution, add 0.121 g of tetramethylammonium bromide to the solution and continue stirring until it is completely dissolved. Heat to 80°C and keep warm for 3 h. Stir continuously during the insulation process to obtain a mixed solution.
[0040] (2) Slowly drip 50 mL of 10% sodium hydroxide solution into the mixed solution obtained in step (1) at a temperature of 80°C for 2 h while stirring continuously. Filter the solution to obtain a cross-linked solid. Dry the solid in a vacuum drying oven at 60°C for 4 h to obtain a dry cross-linked solid.
[0041] (3) placing the cross-linked solid in a hydrogen-argon mixed gas, performing argon pre-cross-linking at 300°C, wherein the hydrogen-argon mixed gas is composed of hydrogen and argon in a volume ratio of 0.1:1, the heating rate is 5°C / min, and the holding time is 1 h, to obtain a pre-treated cross-linked solid;
[0042] (4) The pretreated cross-linked solid obtained in step (3) is placed in a nitrogen environment at 1300°C for high temperature annealing and carbonization, with a heating rate of 5°C / min and a holding time of 2 h. The obtained carbonized solid is a solid oxygen-doped hard carbon electrode material.
[0043] Figure 1 This is the X-ray diffraction (XRD) diagram of the oxygen-doped hard carbon prepared in Example 1. The results show that the material has two bulges at 24° and 43°, corresponding to the (002) crystal plane and the (100) crystal plane respectively, indicating that the impurity-free carbon material has been successfully prepared. The measurement shows that the oxygen-doped hard carbon material has a larger lattice spacing of 0.375 nm, which can make sodium ions receive less resistance when diffusing, which is of great significance to the improvement of energy storage density.
[0044] Figure 2 This is a scanning electron microscope (SEM) image of the oxygen-doped hard carbon electrode material prepared in Example 1. The results show that the material is a porous block solid with mesopores on the surface. The pore size distribution of the mesopores is mainly between 1-30 nm.
[0045] Example 2
[0046] (1) Grind the asphalt with a planetary ball mill, dissolve 1 g of asphalt powder and 0.2 g of urea formaldehyde resin in 5 mL of epifluoropropane, and after complete dissolution, add 0.1 g of benzyltriethylammonium chloride to the solution and continue stirring until it is completely dissolved. Heat to 90°C and keep warm for 3 h. Stir continuously during the insulation process to obtain a mixed solution.
[0047] (2) Slowly drip 50 mL of 30% sodium hydroxide solution into the mixed solution obtained in step (1), keep the temperature at 60°C for 2 h, stir continuously during the heat preservation period, filter the solution to obtain a cross-linked solid, place the solid in a vacuum drying oven, and dry it at 60°C for 4 h to obtain a dry cross-linked solid;
[0048] (3) placing the cross-linked solid obtained in step (2) in a hydrogen-argon mixed gas at 400° C. for hydrogen-argon pre-cross-linking, wherein the hydrogen-argon mixed gas is composed of hydrogen and argon in a volume ratio of 0.1:1, the heating rate is 5° C. / min, and the holding time is 1 h, to obtain a pre-treated cross-linked solid;
[0049] (4) The pretreated cross-linked solid obtained in step (3) is placed in a nitrogen environment at 1400°C for high temperature annealing and carbonization, with a heating rate of 8°C / min and a holding time of 2 h. The obtained carbonized solid is an oxygen-doped hard carbon electrode material.
[0050] Example 3
[0051] (1) Grind cellulose with a planetary ball mill, dissolve 0.5 g of cellulose powder and 0.1 g of m-phenylenediamine in 20 mL of epibromopropane, and after complete dissolution, add 0.2 g of tetramethylammonium bromide to the solution and continue stirring until complete dissolution. Heat the mixed solution to 70°C and keep it warm for 3 h, stirring continuously during the insulation process to obtain a mixed solution;
[0052] (2) Slowly drip 50 mL of 10% potassium hydroxide solution into the mixed solution obtained in step (1), keep the temperature at 50°C for 2 h, stir continuously during the heat preservation period, filter the solution to obtain a cross-linked asphalt solid, place the solid in a vacuum drying oven, and dry it at 60°C for 4 h to obtain a dry cross-linked solid;
[0053] (3) placing the cross-linked solid obtained in step (2) in a hydrogen-argon mixed gas at 500° C. for hydrogen-argon pre-cross-linking, wherein the hydrogen-argon mixed gas is composed of hydrogen and argon in a volume ratio of 0.1:1, the heating rate is 5° C. / min, and the holding time is 1 h, to obtain a pretreated cross-linked solid;
[0054] (4) The pretreated cross-linked solid obtained in step (3) is placed in an argon environment at 1200°C for high-temperature decarbonization, with a heating rate of 2°C / min and a holding time of 2 h to obtain a carbonized solid, which is a bulk oxygen-doped hard carbon electrode material.
[0055] Example 4
[0056] (1) Grind lignin with a planetary ball mill, dissolve 1 g of lignin powder and 1 g of phosphoric acid in 50 mL of epichlorohydrin, and after complete dissolution, add 0.121 g of dodecyltrimethylammonium chloride to the solution and continue stirring until it is completely dissolved. Heat the solution to 80°C and keep it warm for 3 h. Stir continuously during the insulation process to obtain a mixed solution.
[0057] (2) Slowly drip 50 mL of 10% sodium hydroxide solution into the mixed solution obtained in step (1), keep the temperature at 70°C for 2 h, stir continuously during the heat preservation period, filter the solution to obtain a cross-linked solid, place the solid in a vacuum drying oven, and dry it at 60°C for 4 h to obtain a dry cross-linked solid;
[0058] (3) placing the cross-linked solid obtained in step (2) in a hydrogen-argon mixed gas at 600° C. for hydrogen-argon pre-cross-linking, wherein the hydrogen-argon mixed gas is composed of hydrogen and argon in a volume ratio of 0.1:1, the heating rate is 5° C. / min, and the holding time is 1 h, to obtain a pretreated cross-linked solid;
[0059] (4) The pretreated cross-linked solid obtained in step (3) is placed in an argon environment at 1200°C for high-temperature decarbonization, with a heating rate of 3°C / min and a holding time of 2 h to obtain a carbonized solid, which is a bulk oxygen-doped hard carbon electrode material.
[0060] Comparative Example 1
[0061] The asphalt raw material is placed at 1300°C for carbonization treatment to obtain asphalt block carbon.
[0062] Performance Testing
[0063] The oxygen-doped hard carbon prepared in Examples 1-4 and the pitch block carbon material prepared in Comparative Example 1 were respectively used as the negative electrode of the sodium ion battery, and the carbon material (the oxygen-doped hard carbon prepared in Example 1, the oxygen-doped hard carbon prepared in Example 2, the oxygen-doped hard carbon prepared in Example 3, the oxygen-doped hard carbon prepared in Example 4 or the pitch block carbon material prepared in Comparative Example 1), carbon black and polyvinylidene fluoride were mixed in a mass ratio of 8:1:1, deionized water and N-methylpyrrolidone were added and ground in a mortar to prepare a uniform slurry, which was coated on a copper foil and dried in a vacuum drying oven at 60°C. The pole piece was cut into a disc with a diameter of 12 mm as the negative electrode of the sodium ion battery, and the sodium sheet was used as the positive electrode of the sodium ion battery. The electrolyte was 1 mol / L NaClO4 solution, the solute of the NaClO4 solution is NaClO4, and the solvent is diethyl carbonate (DEC) and ethylene carbonate (EC) in a volume ratio of 1:1. The battery is assembled in a glove box filled with argon. The moisture content is less than 0.01 ppm and the oxygen content is less than 0.01 ppm. After the assembly, the battery is subjected to a performance test of the charge and discharge specific capacity.
[0064] Figure 3The charge and discharge specific capacity of the sodium ion battery assembled with the oxygen-doped hard carbon prepared in Examples 1-4 and the pitch block carbon material prepared in Comparative Example 1 at a current density of 30 mA / g. The results show that the first cycle charge capacity of the sodium ion battery assembled with the oxygen-doped hard carbon prepared in Example 1 is 345 mAh g -1 , the discharge capacity is 387 mAh g -1 , the first Coulombic efficiency reached 89%.
[0065] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0066] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A method for preparing oxygen-doped hard carbon for sodium ion batteries, characterized in that: The preparation method comprises the following steps: (1) dissolving a carbon source and a cross-linking agent in an epoxy organic solvent, adding a catalyst, and heating to obtain a mixed solution; (2) adding an alkaline solution to the mixed solution obtained in step (1) to carry out a cross-linking reaction, and obtaining a cross-linked solid after drying; (3) placing the cross-linked solid obtained in step (2) in a hydrogen-argon mixed atmosphere and heating it to obtain a pretreated cross-linked solid; (4) annealing the original cross-linked solid obtained in step (3) to obtain the oxygen-doped hard carbon electrode material for sodium ion battery; Wherein, in step (1), the carbon source is asphalt, lignin or cellulose; the cross-linking agent is m-phenylenediamine, p-phenolamine, melamine, urea-formaldehyde resin or phosphoric acid; In step (1), the mass volume ratio of the carbon source, cross-linking agent, catalyst and epoxy organic solvent is 1 g: (0.05-2) g: (0.01-1) g: (1.12-56) mL; the heating temperature is 40-117°C and the heating time is 0.1-20 h; In step (2), the temperature of the cross-linking reaction is 30-117° C. and the time is 0.1-10 h.
2. The preparation method according to claim 1, characterized in that: The epoxy organic solvent is epichlorohydrin, propylene oxide, epifluorohydrin, epibromohydrin or 3,4-epoxy-1-butene; The catalyst is tetramethylammonium bromide, tetramethylammonium chloride, dodecyltrimethylammonium chloride or benzyltriethylammonium chloride.
3. The preparation method according to claim 1, characterized in that: In step (2), the alkaline solution is a sodium hydroxide solution or a potassium hydroxide solution; The mass concentration of the alkaline solution is 0.1-30%.
4. The preparation method according to claim 1, characterized in that: The volume ratio of the epoxy organic solvent in step (1) to the alkaline solution in step (2) is 1:(0.1-100).
5. The preparation method according to claim 1, characterized in that: In step (3), the hydrogen-argon mixed atmosphere is composed of hydrogen and argon in a volume ratio of (1-0.01):1; The heating temperature is 200-600°C, the heating time is 0.1-5 h, and the heating rate is 1-10°C / min.
6. The preparation method according to claim 1, characterized in that: In step (4), the annealing treatment is carried out in a nitrogen or argon atmosphere; the annealing treatment temperature is 800-1600°C, the time is 0.5-6 h, and the heating rate is 1-10°C / min.
7. The oxygen-doped hard carbon electrode material for sodium ion battery prepared by the method according to any one of claims 1 to 6, characterized in that: The surface of the oxygen-doped hard carbon electrode material for sodium ion batteries contains mesopores with a pore size of 1-30 nm.
8. Use of the oxygen-doped hard carbon electrode material for sodium ion battery prepared by the method according to any one of claims 1 to 6 and / or the oxygen-doped hard carbon electrode material for sodium ion battery according to claim 7, characterized in that: The oxygen-doped hard carbon electrode material for sodium ion batteries is used in the field of sodium ion batteries.
Citation Information
Patent Citations
Hard carbon cathode material for power energy storage battery and preparation method thereof
CN103754858A
Plasma method modified hard carbon composite material as well as preparation method and application thereof
CN117174860A